Mathematical Thermal Time Model to Explain Seed Germination - Naim, Atif Hassan (International Journal For Research In Agricultural And Food Science, 2016)
Seed germination is an intricate physiological process which commences as the seed coat imbibes water and culminates in emergence of the radicle or hypocotyl. The rate of water uptake depends largely on the gradient of water potential between the non-dormant seed and the growth medium. A reduction in water potential of the surrounding growth medium will reduce the rate of water uptake by the seed because the gradient between them is less (Finch-Savage, 2004).